Answer:
Step-by-step explanation:
5x + 3 = 2x - 6
3x + 3 = -6
3x = -9
x = -3
Answer:
4 (x + 7) = 8
Step-by-step explanation:
4 (x + 7) = 8 Because you add 7 to Amy's number then multiplied by 4 which equals 8
You can answer this problem in two different ways: the first being (17 - 5) * x, and the second being 12 * x.
Answer:
x=−18
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
12+2x=x−6
12+2x=x+−6
2x+12=x−6
Step 2: Subtract x from both sides.
2x+12−x=x−6−x
x+12=−6
Step 3: Subtract 12 from both sides.
x+12−12=−6−12
x=−18